Implementation Of Sharia Business Ethics On The Roadside Muslim Traders Around The University Of Muhammadiyah Sumatera Utara (Umsu) Medan - Efry Kurnia; Uswah Hasanah (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this research is to know and analyze the activities of the roadside Muslims around the campus UMSU Medan and to know the implementation of Islamic business ethics in the business of the roadside Muslims around UMSU Medan. This type of research is qualitative descriptive research through interview and observation taking and questionnaires. The results obtained by Muslim traders around the UMSU do not do adverse elements for the buyer or consume generally in the perspective of Islamic Shariah studies. In this implementation of Islamic business ethics includes four aspects: principle, management, marketing/advertising and product/price.